Exploring the Role of Family Economic Education in Meeting Economic Demands, Sociocultural Dynamics, and Enhancing Economic Literacy - Hendra Rustantono; Hamidi Rasyid; Tety Nur Cholifah; Yulia Eka Yanti; Sumiharti Sumiharti; Sainil Amral; Trio Saputra; Zuhri Saputra Hutabarat (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates how family economic education influences students' financial behaviors, focusing on managing consumptive tendencies. Five hypotheses are used in this study, which employs quantitative statistical analysis techniques. One hundred and fifty of the 340 students enrolled in the Economics Education department at Jambi University were chosen for the study. The study's conclusions show that: 1) A student's financial management and consumption behavior are influenced by the kind of economic education they receive at home; 2) Family economic education gives guidance on socio-cultural order and economic literacy, helping to shape a child's non-consumptive personal character; 3) Having a solid understanding of economic demands allows one to plan ahead financially and make prudent financial decisions; 4) Students have a lot of understanding to change behavior from unintelligent to intelligent in understanding economic literacy and family economic education; and 5) Through order socio-cultural lifestyle through family economic education, students no longer follow excessive styles, based on careful consideration and in accordance with needs. This study came to the conclusion that in order for students to overcome their financial challenges, which include engaging in consumption activities, they must be able to master and apply economic knowledge acquired from family economic education, economic demands, socio-cultural order, and economic literacy in everyday life.